ANTICUERPOS CONTRA EL VIRUS DE LA ESTOMATITIS VESICULAR EN SAJINOS (Tayassu tajacu) DE ZOOCRIADEROS DE IQUITOS Y PUCALLPA - Wilson D., Aldo (2005)
The objetive of this study was to detect antibodies against vesicular stomatitisvirus (VSV) in collared peccaries (Tayassu tajacu) from farms of Iquitos and Pucallpa,Peru. Blood samples were collected in animals olders than 6 months of age (pregnantfemales were not included) from a farm in Iquitos (n = 21) and from four farms in Pucallpa(n = 47), for detection of antibodies against Indiana 1 and New Jersey serotype of VSVby viral neutralization test. No specific antibodies against both serotypes of VSV weredetected, indicating that the peccaries were not exposed to VSV, and suggesting absenceof the infection in those animals.